1994
DOI: 10.1002/sca.4950160313
|View full text |Cite
|
Sign up to set email alerts
|

Highly controllable fabrication of fiber probe for photon scanning tunneling microscope

Abstract: Summary: A selective chemical etching was used to fabricate fiber probes for the photon scanning tunneling microscope (PSTM). The cladding diameter of the fiber probe was controlled by varying the first-step etching time. The cone angle of the fiber probe tip was controlled by varying the doping ratio of the fiber and the composition of the etching solution. A cladding diameter of 8 µm and a tip diameter of about 3 nm were fabricated. The smallest cone angle was 14°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 13 publications
(17 reference statements)
0
0
0
Order By: Relevance
“…It was found that tip dimensions are influenced by a volume ratio of HF and NH4F in etching solutions and by etching time [53]. It is worth mentioning that in addition to etching solutions containing HF (usually approximately 50% wgt.…”
Section: Fiber Nanotip Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that tip dimensions are influenced by a volume ratio of HF and NH4F in etching solutions and by etching time [53]. It is worth mentioning that in addition to etching solutions containing HF (usually approximately 50% wgt.…”
Section: Fiber Nanotip Preparationmentioning
confidence: 99%
“…It is worth mentioning that in addition to etching solutions containing HF (usually approximately 50% wgt. ), buffered etching aqueous solutions employing HF and NH 4 F have also been used for the preparation of fiber nanotips [53]. Chemical reactions during etching with such etching solutions can be generally described by Equations ( 1) and ( 2) and by Equations ( 3) and (4) as well.…”
Section: Fiber Nanotip Preparationmentioning
confidence: 99%
See 1 more Smart Citation